Epoxy conductive silver glue for chip connection and preparation method thereof

By using nano silver powder and poly3,4-ethylenedioxythiophene-polyethylene glycol copolymer to form a composite material and adding graphene, the problems of low thermal conductivity, high resistivity and poor adhesion in chip connections are solved, and the high conductivity, thermal conductivity and adhesion properties are improved.

CN119060672BActive Publication Date: 2025-03-21CHIZHOU KECHENG NEW MATERIALS DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411571895.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing conductive silver glue has problems such as low thermal conductivity, high resistivity and poor adhesion in chip connections, resulting in problems such as signal attenuation, delay and unstable adhesion in high-frequency circuits and high-temperature environments.

Method used

An epoxy conductive silver glue for chip connection is used, which includes nano silver powder as the conductive main material. By forming a stable composite material with poly3,4-ethylenedioxythiophene-polyethylene glycol copolymer, the conductivity and adhesion are improved, and trace amounts of graphene are added to the matrix to reduce thermal resistance.

Benefits of technology

It significantly improves the conductivity, thermal conductivity and bonding properties of conductive silver glue, and can transfer heat and electrical signals more effectively. It is suitable for chip small chips, metal frames and high-precision dispensing packaging processes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of conductive adhesive materials, and in particular to an epoxy conductive silver adhesive for chip connection and a preparation method thereof, which comprises the following components by mass percentage: 2-20% epoxy resin, 1-10% diluent, 0.2-1% thixotropic agent, 0.01-0.1% graphene, 1-10% curing agent, 0.1-0.5% curing accelerator, 70-80% conductive main material, 5-10% conductive auxiliary material, 0.1-2.5% defoaming agent and 0.1-2.5% coupling agent. The epoxy conductive silver adhesive prepared by the present invention has high conductivity, good thermal conductivity, low resistivity, strong adhesion and stable electrical properties, and can be applied to high-precision fields such as small chips, metal frames, and dispensing packaging processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive adhesive materials, and in particular to epoxy conductive silver adhesive for chip connection and a preparation method thereof. Background Art

[0002] Epoxy conductive silver glue is a high-performance electronic packaging material, the main components of which include epoxy resin, silver powder and curing agent. During the packaging process, epoxy conductive silver glue is cured by heating to tightly connect the chip to the substrate or other electronic components to form a mechanical fixation and electrical path. This connection method not only provides good mechanical support and environmental protection, but also ensures the unobstructed current path and signal path, while providing a thermal path to dissipate the heat generated by the semiconductor chip.

[0003] In the prior art, compared with pure metal or alloy solder interconnection, conductive silver paste has the disadvantages of low thermal conductivity, high resistivity, and poor adhesion. The silver particles in the conductive silver paste are wrapped by the matrix, forming a thermal resistance between the particles. Pure metal or alloy solder can transfer heat more effectively due to its continuous metal structure. Secondly, the resistivity of conductive silver paste is relatively high, which affects the energy loss and signal transmission quality in the circuit, especially in high-frequency circuits such as chips, where high resistivity may cause signal attenuation and delay. In addition, the adhesion of conductive silver paste mainly depends on the adhesion between epoxy resin and the connection surface. During long-term use or in a high-temperature environment, the conductive silver paste will have problems with weak adhesion or falling off, aging or degradation, and further reduce its bonding performance. Summary of the invention

[0004] In order to solve the problems mentioned in the above background technology, the present invention provides an epoxy conductive silver paste for chip connection and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The invention discloses an epoxy conductive silver glue for chip connection, which comprises the following components by mass percentage: 2-20% of epoxy resin, 1-10% of diluent, 0.2-1% of thixotropic agent, 0.01-0.1% of graphene, 1-10% of curing agent, 0.1-0.5% of curing accelerator, 70-80% of conductive main material, 5-10% of conductive auxiliary material, 0.1-2.5% of defoaming agent and 0.1-2.5% of coupling agent, wherein the conductive main material is nano silver powder, which comprises one or two of nano flaky silver powder, nano spherical silver powder and silver nanowire, the diameter of the nano flaky silver powder is 5-100nm, the particle diameter of the nano spherical silver powder is 5-50nm, and the diameter of the silver nanowire is 10-100nm. The epoxy conductive silver glue is applied to small chips, metal frames and dispensing packaging processes.

[0007] Further, the epoxy resin includes one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol A type epoxy resin and tetraglycidylamine type epoxy resin.

[0008] Further, the diluent includes one or more of dodecyl glycidyl ether, 1,4-butanediol glycidyl ether, phenyl glycidyl ether and polyhydroxy polyether.

[0009] Further, the thixotropic agent includes one or more of hydrogenated castor oil, polyamide wax and fumed silica.

[0010] Further, the curing agent includes one or more of m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone and m-phenylenediamine, and the curing accelerator includes one or more of 2-ethyl-4-methylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol and boron trifluoride-triethylamine complex.

[0011] Further, the defoaming agent includes one or more of 6201, BYK-141 or BYK-053, and the coupling agent includes one or both of KH550 and KH560.

[0012] Furthermore, the conductive auxiliary material is prepared by the following steps:

[0013] Ethylene glycol, deionized water and 3,4-ethylenedioxythiophene are sequentially added into a reactor, polyvinyl pyrrolidone is added into the reactor, stirred until uniformly dispersed, placed in an ice water bath, the reaction temperature is maintained at 0-5°C using a temperature controller, 0.1-0.2 mol / L ammonium persulfate solution is prepared with deionized water, the ammonium persulfate solution is slowly dripped into the reactor using a constant pressure dropping funnel at a stirring speed of 50-100 rpm, the dripping speed is controlled at 10-20 drops per minute to avoid local overheating and sudden polymerization, after the dripping is completed, the reaction is carried out for 12-24 hours, nano silver powder is added into the reaction solution, and the stirring is continued at a speed of 50-100 rpm for 1-2 hours, 0.2-0.22 mol / L sodium thiosulfate solution is added to terminate the polymerization reaction, the reaction solution is poured into 1 L of deionized water, filtered, washed, and dried to constant weight at room temperature to obtain a conductive auxiliary material.

[0014] Furthermore, the mass ratio of ethylene glycol, 3,4-ethylenedioxythiophene, polyvinyl pyrrolidone, ammonium persulfate, nano silver powder and sodium thiosulfate is (6-7): (14-15): 50: (0.7-0.9): (10-20): (0.5-0.55), the nano silver powder is selected from the conductive main material, and the molar ratio of ethylene glycol, 3,4-ethylenedioxythiophene and nano silver powder is (1-1.1): (1-1.05): (0.93-1.86).

[0015] According to another aspect of the present invention, a method for preparing the above-mentioned epoxy conductive silver paste is provided, comprising the following steps:

[0016] S1. Add epoxy resin, diluent, thixotropic agent, graphene, curing agent, curing accelerator, defoaming agent and coupling agent into a homogenizing tank according to mass percentage, put it into a homogenizer, and perform vacuum homogenization at a speed of 1000-2000rpm for 2-3min to obtain a conductive adhesive base material;

[0017] S2. Add the conductive main material and the conductive auxiliary material into the conductive adhesive base material, put it into a homogenizer and perform vacuum homogenization at a speed of 1000-2000 rpm for 2-3 minutes to obtain a conductive adhesive product.

[0018] Beneficial effects of the present invention:

[0019] 1. In the technical solution of the present invention, the nano silver powder in the conductive auxiliary material is evenly dispersed in the poly (3,4-ethylenedioxythiophene)-polyethylene glycol copolymer matrix. After copolymerization of poly (3,4-ethylenedioxythiophene) (PEDOT) and polyethylene glycol (PEG), its long chain structure can entangle and coat the nano silver powder to form a stable composite material, thereby enhancing the stability of the nano silver powder and improving its compatibility with the epoxy resin matrix. As the main conductive material, nano silver powder provides the main electron transmission channel. Its high conductivity and good dispersibility ensure the smooth transmission of current in the material. Poly (3,4-ethylenedioxythiophene) itself has a certain conductivity. After copolymerization with polyethylene glycol, it further enhances the conductive properties of the material while improving the flexibility and processability of the composite material, which helps to maintain the integrity of the conductive network.

[0020] 2. In the technical solution of the present invention, adding a small amount of graphene to the epoxy conductive silver paste can form an effective heat conduction path in the matrix, significantly reduce thermal resistance, and improve overall thermal conductivity. The graphene layer structure can increase the contact area of ​​heat conduction, allowing heat to be transferred more quickly.

[0021] 3. The epoxy conductive silver paste prepared by the present invention has high conductivity, good thermal conductivity, low resistivity, strong adhesion and stable electrical properties, and can be applied to high-precision fields such as small chips, metal frames, and dispensing packaging processes. DETAILED DESCRIPTION

[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.

[0024] Preparation Example 1

[0025] The conductive auxiliary material is prepared by the following steps:

[0026] 6 g of ethylene glycol, 50 mL of deionized water and 14 g of 3,4-ethylenedioxythiophene were added to the reactor in sequence, 50 g of polyvinyl pyrrolidone was added to the reactor, stirred until uniformly dispersed, placed in an ice water bath, and the reaction temperature was maintained at 0°C using a temperature controller. 0.1 mol / L ammonium persulfate solution was prepared with deionized water, and 150 mL of ammonium persulfate solution was slowly added to the reactor using a constant pressure dropping funnel at a stirring speed of 50 rpm. The dropping speed was controlled at 10 drops per minute. After the addition was completed, the reaction was continued for 12 hours, and 10 g of nano-spherical silver powder was added to the reaction solution, and stirring was continued at a speed of 50 rpm for 1 hour. 14 mL of 0.2 mol / L sodium thiosulfate solution was added, and the reaction solution was poured into 1 L of deionized water, filtered, washed, and dried to constant weight at room temperature to obtain a conductive auxiliary material.

[0027] Preparation Example 2

[0028] The conductive auxiliary material is prepared by the following steps:

[0029] 6.5 g of ethylene glycol, 50 mL of deionized water and 14.5 g of 3,4-ethylenedioxythiophene were added to the reactor in sequence, 50 g of polyvinyl pyrrolidone was added to the reactor, stirred until uniformly dispersed, placed in an ice water bath, and the reaction temperature was maintained at 2°C using a temperature controller. 0.15 mol / L ammonium persulfate solution was prepared with deionized water, and 175 mL of ammonium persulfate solution was slowly added to the reactor using a constant pressure dropping funnel at a stirring speed of 60 rpm. The dropping speed was controlled at 15 drops per minute. After the addition was completed, the reaction was continued for 18 hours, and 15 g of nano-flaky silver powder was added to the reaction solution, and stirring was continued at a speed of 60 rpm for 1.5 hours. 20 mL of 0.21 mol / L sodium thiosulfate solution was added, and the reaction solution was poured into 1 L of deionized water, filtered, washed, and dried to constant weight at room temperature to obtain a conductive auxiliary material.

[0030] Preparation Example 3

[0031] The conductive auxiliary material is prepared by the following steps:

[0032] 7g of ethylene glycol, 50mL of deionized water and 15g of 3,4-ethylenedioxythiophene were added to the reactor in sequence, 50g of polyvinyl pyrrolidone was added to the reactor, stirred until uniformly dispersed, placed in an ice water bath, and the reaction temperature was maintained at 5°C using a temperature controller. 0.2mol / L ammonium persulfate solution was prepared with deionized water, and 200mL of ammonium persulfate solution was slowly added to the reactor using a constant pressure dropping funnel at a stirring speed of 100rpm. The dropping speed was controlled at 20 drops per minute. After the addition was completed, the reaction was continued for 24h, 20g of silver nanowires were added to the reaction solution, and stirring was continued at a speed of 100rpm for 2h, 25mL of 0.22mol / L sodium thiosulfate solution was added, the reaction solution was poured into 1L of deionized water, filtered, washed, and dried to constant weight at room temperature to obtain a conductive auxiliary material. Example 1

[0033] A method for preparing epoxy conductive silver glue for chip connection comprises the following steps:

[0034] S1, weigh 10g bisphenol A epoxy resin, 5g dodecyl glycidyl ether, 0.5g hydrogenated castor oil, 0.05g graphene, 5g m-phenylenediamine, 0.3g 2-ethyl-4-methylimidazole, 1g 6201 and 0.2g KH550, add them into a homogenizing tank, put it into a homogenizer, and perform vacuum homogenization at a speed of 1000rpm for 2min to obtain a conductive adhesive base material;

[0035] S2. Add 70 g of nano-flaky silver powder and 8 g of the conductive auxiliary material obtained in Preparation Example 1 to the conductive adhesive base material, put it into a homogenizer and perform vacuum homogenization at a speed of 1000 rpm for 2 minutes to obtain 100 g of a conductive adhesive product. Example 2

[0036] A method for preparing epoxy conductive silver glue for chip connection comprises the following steps:

[0037] S1, weigh 15g bisphenol F epoxy resin, 7g 1,4-butanediol glycidyl ether, 0.5g polyamide wax, 0.1g graphene, 6g diaminodiphenylmethane, 0.4g 2,4,6-tris(dimethylaminomethyl)phenol, 1g BYK-141 and 0.2g KH560, add them into a homogenizing tank, put them into a homogenizer, and perform vacuum homogenization at a speed of 1500rpm for 2.5min to obtain a conductive adhesive base material;

[0038] S2. Add 73 g of nano-spherical silver powder and 5 g of the conductive auxiliary material obtained in Preparation Example 2 to the conductive adhesive base material, put it into a homogenizer and perform vacuum homogenization at a speed of 1500 rpm for 2.5 min to obtain 100 g of a conductive adhesive product. Example 3

[0039] A method for preparing epoxy conductive silver glue for chip connection comprises the following steps:

[0040] S1, weigh 12g hydrogenated bisphenol A epoxy resin, 4g phenyl glycidyl ether, 0.3g fumed silica, 0.02g graphene, 4g diaminodiphenyl sulfone, 0.2g 2-ethyl-4-methylimidazole, 1.5g BYK-053 and 0.5g KH550, add them into a homogenizing tank, put them into a homogenizer, and perform vacuum homogenization at a speed of 2000rpm for 3min to obtain a conductive adhesive base material;

[0041] S2. Add 75 g of silver nanowires and 6 g of the conductive auxiliary material obtained in Preparation Example 3 to the conductive adhesive base material, put it into a homogenizer and perform vacuum homogenization at a speed of 2000 rpm for 3 minutes to obtain 100 g of a conductive adhesive product.

[0042] Comparative Example 1

[0043] The difference between this comparative example and Example 1 is that poly (3,4-ethylenedioxythiophene) is used as the conductive auxiliary material, and the remaining steps are the same as those of Example 1.

[0044] Comparative Example 2

[0045] The difference between this comparative example and Example 2 is that polyethylene glycol is used as the conductive auxiliary material, and the remaining steps are the same as those in Example 2.

[0046] Comparative Example 3

[0047] The difference between this comparative example and Example 3 is that silver nanowires are used as conductive auxiliary materials, and the remaining steps are the same as those of Example 3.

[0048] (I) Conductivity test

[0049] The conductive adhesives obtained in Examples 1-3 and Comparative Examples 1-3 were baked at 175° C. and 300° C. for 1 hour, respectively, and cured. The volume resistivity was tested by a four-probe method. The results are shown in Table 1:

[0050] Table 1. Volume resistivity results of Examples 1-3 and Comparative Examples 1-3

[0051] serial number temperature Resistivity (Ω·cm) Example 1 175℃ <![CDATA[4.1×10 -4 ]]> 300℃ <![CDATA[7.5×10 -5 ]]> Example 2 175℃ <![CDATA[4.3×10 -4 ]]> 300℃ <![CDATA[7.2×10 -5 ]]> Example 3 175℃ <![CDATA[4.4×10 -4 ]]> 300℃ <![CDATA[7.8×10 -5 ]]> Comparative Example 1 175℃ <![CDATA[6.5×10 -4 ]]> 300℃ <![CDATA[1.9×10 -4 ]]> Comparative Example 2 175℃ <![CDATA[8.4×10 -4 ]]> 300℃ <![CDATA[1.5×10 -4 ]]> Comparative Example 3 175℃ <![CDATA[5.7×10 -4 ]]> 300℃ <![CDATA[9.1×10 -5 ]]>

[0052] Select several copper foils with a purity of ≥99.9% as the conductor material with a thickness of 0.1±0.05mm, and select several polyimides (PI) as the insulating substrate with a thickness of 0.2mm. Cut the conductor material into 10mm×10mm squares, and clean the surface of the conductor material. Coat a layer of conductive glue prepared in Examples 1-3 and Comparative Examples 1-3 on each insulating substrate, and then paste the conductive material thereon for shaping. Set up another control group, and use solder (Sn63Pb37) instead of conductive glue. Use a four-wire contact resistance tester (RM3545) to test the contact resistance at 25±1℃ and 45%RH. The results are shown in Table 2:

[0053] Table 2. Contact resistance results of Examples 1-3, Comparative Examples 1-3 and Control Group

[0054] serial number Contact resistance (Ω) Example 1 0.96 Example 2 0.94 Example 3 0.91 Comparative Example 1 1.04 Comparative Example 2 1.18 Comparative Example 3 1.01 Control group 0.74

[0055] (II) Thermal conductivity test

[0056] A heat-resistant glue is pasted on the inner wall of the cylindrical mold, and the conductive glue prepared in Examples 1-3 and Comparative Examples 1-3 is poured into the mold respectively. The mold is placed in a drying oven and dried at 90°C for 24 hours, then heated to 200°C and cured for 2 hours. The sample is taken out to obtain a sample with a thickness of 1±0.5 μm.

[0057] The samples of Examples 1-3 and Comparative Examples 1-3 were placed in a differential thermal analyzer (TG-DSC) for thermal performance analysis. The test temperature was 175-300°C, the atmosphere was air, the heating rate was 5°C / min, and the thermal conductivity was tested using a laser thermal conductivity meter. The results are shown in Table 3:

[0058] Table 3. Thermal conductivity results of Examples 1-3 and Comparative Examples 1-3

[0059] serial number Thermal conductivity (W / (mK)) Example 1 114.74 Example 2 110.12 Example 3 114.87 Comparative Example 1 104.19 Comparative Example 2 98.40 Comparative Example 3 106.23

[0060] (III) Adhesion test

[0061] The conductive adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were made into pressureless solidified solder joint samples, and tested using a push-pull tester. The transverse shear rate of the probe was 200 μm / s, the probe descending speed was 400 μm / s, and the shear height was 100 μm. Each solder joint sample was fixed on a heating table that had reached 175° C. and a shear strength test was performed. The results are shown in Table 4:

[0062] Table 4. Shear strength results of Examples 1-3 and Comparative Examples 1-3

[0063] serial number Shear strength(MPa) Example 1 92.37 Example 2 89.49 Example 3 91.35 Comparative Example 1 85.97 Comparative Example 2 76.82 Comparative Example 3 87.08

[0064] It can be seen from Table 1 and Table 2 that the volume resistivity of the conductive adhesives of Examples 1-3 at 175°C and 300°C are lower than those of Comparative Examples 1-3, and the contact resistance of the conductive adhesives of Examples 1-3 is closer to the contact resistance of the control group solder (Sn63Pb37), indicating that the conductive adhesives in the examples have better conductive properties, which may be due to the better composite effect of the conductive main materials and conductive auxiliary materials in the examples with base materials such as epoxy resin, forming a more complete conductive network, improving its dispersibility and compatibility in epoxy resin, and thus enhancing the conductive properties.

[0065] As can be seen from Table 3, the thermal conductivity of Examples 1-3 is higher than that of Comparative Examples 1-3, indicating that the conductive main material and auxiliary material in the examples form a more effective thermal conduction channel with the base material. The conductive auxiliary material in the examples may improve its dispersibility and compatibility in the epoxy resin, thereby improving the thermal conductivity. The conductive auxiliary material used in Comparative Examples 1-3 may not be able to form an effective thermal conduction channel, so the thermal conductivity is low.

[0066] As shown in Table 4, the shear strength of Examples 1-3 is higher than that of Comparative Examples 1-3, indicating that the conductive adhesive in the examples has better bonding performance. The conductive adhesive in the examples may form a stronger chemical bonding effect, thereby improving the cohesion and adhesion of the conductive adhesive.

[0067] In summary, the conductive adhesives prepared in Examples 1-3 have high electrical conductivity as well as good thermal conductivity and bonding properties.

[0068] In the description of the specification, the description with reference to the terms "preparation example", "embodiment", "various embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or preparation example are included in at least one embodiment or preparation example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or preparation example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or preparation examples in a suitable manner.

[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An epoxy conductive silver paste for chip connection, characterized in that: The composition comprises the following components by mass percentage: 2-20% epoxy resin, 1-10% diluent, 0.2-1% thixotropic agent, 0.01-0.1% graphene, 1-10% curing agent, 0.1-0.5% curing accelerator, 70-80% conductive main material, 5-10% conductive auxiliary material, 0.1-2.5% defoaming agent and 0.1-2.5% coupling agent, wherein the conductive main material is nano silver powder; Wherein, the conductive auxiliary material is prepared by the following steps: Ethylene glycol, deionized water and 3,4-ethylenedioxythiophene are sequentially added into a reactor, polyvinyl pyrrolidone is added, and the reactor is placed in an ice water bath. A temperature controller is used to maintain the reaction temperature at 0-5°C, and a 0.1-0.2 mol / L ammonium persulfate solution is prepared with deionized water. The ammonium persulfate solution is added dropwise under stirring. After the addition is completed, the reaction is carried out for 12-24 hours, and nano silver powder is added into the reaction solution, and the stirring is continued for 1-2 hours. A sodium thiosulfate solution is added to terminate the polymerization reaction, and the reaction solution is poured into 1 L of deionized water, filtered, washed, and dried to constant weight at room temperature to obtain a conductive auxiliary material; In the conductive auxiliary material step, the mass ratio of ethylene glycol, 3,4-ethylenedioxythiophene, polyvinyl pyrrolidone, ammonium persulfate, nano silver powder and sodium thiosulfate is (6-7): (14-15): 50: (0.7-0.9): (10-20): (0.5-0.8).

2. The epoxy conductive silver paste for chip connection according to claim 1, characterized in that: The epoxy resin includes one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, hydrogenated bisphenol A type epoxy resin and tetraglycidylamine type epoxy resin.

3. The epoxy conductive silver paste for chip connection according to claim 1, characterized in that: The diluent includes one or more of dodecyl glycidyl ether, 1,4-butanediol glycidyl ether, phenyl glycidyl ether and polyhydroxy polyether.

4. The epoxy conductive silver paste for chip connection according to claim 1, characterized in that: The thixotropic agent includes one or more of hydrogenated castor oil, polyamide wax and fumed silica.

5. The epoxy conductive silver paste for chip connection according to claim 1, characterized in that: The curing agent includes one or more of m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone and m-phenylenediamine, and the curing accelerator includes one or more of 2-ethyl-4-methylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol and boron trifluoride-triethylamine complex.

6. The epoxy conductive silver paste for chip connection according to claim 1, characterized in that: The defoaming agent includes one or more of 6201, BYK-141 or BYK-053, and the coupling agent includes one or two of KH550 and KH560.

7. The method for preparing the epoxy conductive silver paste for chip connection according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Add epoxy resin, diluent, thixotropic agent, graphene, curing agent, curing accelerator, defoaming agent and coupling agent into a homogenizing tank according to mass percentage, put it into a homogenizer, and perform vacuum homogenization at a speed of 1000-2000rpm for 2-3min to obtain a conductive adhesive base material; S2. Add the conductive main material and the conductive auxiliary material into the conductive adhesive base material, put it into a homogenizer and perform vacuum homogenization at a speed of 1000-2000 rpm for 2-3 minutes to obtain a conductive adhesive product.

Citation Information

Patent Citations

  • Epoxy conductive resin applicable to binding of LED (light-emitting diode) chips, and preparation method thereof

    CN102634313A

  • Method for in-situ synthesis of PEDOT (poly(3,4-ethylenedioxythiophene)) / nano silver transparent conductive coating

    CN104861189A